PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH SPONSORSHIP TERHADAP NIAT BELI ULANG - Yogi Arta Wiguna, I Putu; Santika, I Wayan (E-Jurnal Manajemen; Vol 9 No 1 (2020)DO - 10.24843/EJMUNUD.2020.v09.i01.p11, 2020)
The purpose of this study was to determine the role of brand image in mediating the effect of sponsorship on repurchase intention. This research was conducted at Old Man’s Café Canggu Bali. The study population was visitors who consumed X drinks more than once with a sample of 100 respondents. The analysis technique used is path analysis technique. The results of the study indicate that Sponsorship has a positive and significant effect on X brand drinks at Old Man’s Bar in Canggu. Sponsorship has a positive and significant effect on the intention to repurchase drink X at Old’s Man Bar in Canggu. Brand image has a positive and significant effect on the intention to repurchase drinks X Old Man’s Bar in Canggu Brand image significantly mediates the relationship between sponsorship variables and repurchase intention . Keywords: brand image, sponsorship, repurchase intention